Mechanics of pH-responsive hydrogel capsules - Best, James P.; Neubauer, Martin P.; Javed, Sameen; Dam, Henk H.; Fery, Andreas; Caruso, Frank (Langmuir, 2013)
While soft hydrogel nano- and microstructures hold great potential for therapeutic treatments and in vivo applications, their nanomechanical characterization remains a challenge. In this paper, soft, single-component, supported hydrogel films were fabricated using pendant-thiol-modified poly(methacrylic acid) (PMASH). The influence of hydrogel architecture on deformation properties was studied by fabricating films on particle supports and producing free-standing capsules. The influence of the degree of thiol-based cross-linking on the mechanical properties of the soft hydrogel systems (core-shell and capsules) was studied using a colloidal-probe (CP) AFM technique. It was found that film mechanical properties, stability, and capsule swelling could be finely tuned by controlling the extent of poly(methacrylic acid) thiol modification. Furthermore, switching the pH from 7.4 to 4.0 led to film densification due to increased hydrogen bonding. Hydrogel capsule systems were found to have stiffness values ranging from 0.9 to 16.9 mN m-1 over a thiol modification range of 5 to 20 mol %. These values are significantly greater than those for previously reported PMASH planar films of 0.7-5.7 mN m-1 over the same thiol modification range (Best et al., Soft Matter 2013, 9, 4580-4584). Films on particle substrates had comparable mechanical properties to planar films, demonstrating that while substrate geometry has a negligible effect, membrane and tension effects may play an important role in capsule force resistance. Further, when transitioning from solid-supported films to free-standing capsules, simple predictions of shell stiffness based on modulus changes found for supported films are not valid. Rather, additional effects like diameter increases (geometrical changes) as well as tension buildup need to be taken into account. These results are important for research related to the characterization of soft hydrogel materials and control over their mechanical properties. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20